Threats and Challenges of Smart Grids Deployments - A Developing Nations’ Perspective (ELEKTRIKA- Journal of Electrical Engineering, 2019)
Considerable efforts in huge investments are being made to achieve a resilient Smart Grids (SGs) deployment for the improvement of power delivery scheme. Unsurprisingly, many developing nations are making slow progress to the achievement of this feat which is set to revolutionize the power industry own to several deployment and security issues. Studying these challenges from both technical and non-technical view, this paper presents a highlight and assessment of each of the identified challenges. These challenges are assessed by exposing the security and deployment related threats while suggesting ways of tackling these challenges with prominence to developing nations. Although, a brief highlight, this review will help key actors in the region to identify the related challenges and it’s a guide to sustainable deployments of SGs in the region
Keywords: Challenges; Developing Nations; Deployment; Smart Grid; Threats